Redesigning carbon emissions reduction policies for China’s manufacturing industry: a dynamic stochastic general equilibrium approach - Lei, Yutao; Zhang, Xuan; Yao, Canzhong; Peng, Wenxiang (Frontiers in Energy Research, 2023)
This paper develops a dynamic stochastic general equilibrium (DSGE) model of China’s manufacturing industry and investigates the impact of innovation on environmental protection technology, the carbon emissions tax, and government emissions reduction expenditures on the output and carbon emissions reduction of China’s manufacturing industry. Unlike previous studies that examined one policy using a single model, by focusing on the differences between three shocks it is possible to make the policies more comparable. The results indicate that updating environmental protection technology can promote the development of the manufacturing industry and reduce carbon emissions in the short term. Carbon emissions taxes have a negative effect on manufacturing output in the short term and a significant and lasting effect on the reduction of carbon emissions in the long term. The government’s emissions reduction expenditures have a positive effect on manufacturing output in the short term, but a non-significant negative effect in the long term. The Chinese government should take the lead in implementing carbon emissions tax policies in heavily polluting industries and regions while lowering but stabilizing emissions reduction expenditures.